Online Scratch Activities during the COVID-19 Pandemic: Computational and Creative Thinking - Didem Karakaya Cırıt; Selçuk Aydemir (Institute of Advanced Engineering and Science, 2023)
This paper investigated the effect of online Scratch activities on college students’ computational and creative thinking. The study adopted a mixed research design including one group pretest-posttest. The sample consisted of 24 child development undergraduates (23 female and 1 male) in the 2019-2020 academic year. The research was carried out in